Geographic variation in the yield formation of single-season high-yielding hybrid rice in southern China - Dan-ying WANG; Xu-yi LI; Chang YE; Chun-mei XU; Song CHEN; Guang CHU; Yun-bo ZHANG; Xiu-fu ZHANG (Journal of Integrative Agriculture, 2021)
Environmental conditions greatly affect the growth of rice. To investigate the geographic differences in yield formation of single-season high-yielding hybrid rice in southern China, experiments were conducted in 2017 and 2018 in the upper and middle–ower reaches of the Yangtze River with 10–30 main locally planted high-yielding hybrid cultivars used as materials. Compared with rice planted in the middle–lower reaches of the Yangtze River, rice planted in the upper reaches has a longer tillering duration, higher accumulated temperature (≥10°C) during tillering period, but lower accumulated temperature and solar radiation from initial booting to maturity. Yield traits comparison between the upper and the middle–lower reaches of Yangtze River showed that the former had 48.1% more panicles per unit area while the latter had 46.4% more grains per panicle; the rice yield in the former was positively correlated with the seed setting rate and the dry matter accumulation before heading, while the latter was positively correlated with grains per panicle and dry matter accumulation from booting to maturity. Comparison of the same variety Tianyouhuazhan planted in different regions showed there was a significant positive correlation between panicle number and the duration of and accumulated temperature during the tillering period (r=0.982**, r=0.993**, respectively), and between grains per panicle and accumulated solar radiation during booting period (r=0.952*). In the upper reaches of the Yangtze River, more than 90% of cultivars with an yield of greater than 11 t ha–1 had an effective panicle number of 250–340 m–2, and there was a significant negative correlation between seed setting rate and grains per panicle; therefore, the high-yielding rice production in these regions with a long effective tillering period (>40 d) should choose varieties with moderate grains per panicle, adopt crop managements such as good fertilizer and water measures during vegetative growth period to ensure a certain number of effective panicles, and to increase the dry matter accumulation before heading. While in regions with a short effective tillering period (<20 d) but good sunshine conditions during the reproductive growth period, such as the middle–lower reaches of the Yangtze River, high-yielding rice production should choose cultivars with large panicles, adopt good water and fertilizer managements during the reproductive growth period to ensure the formation of large panicles and the increase of dry matter accumulation after heading.